No clear benefit of transcutaneous auricular vagus nerve stimulation for non-native speech sound learning - Honda, Claire T.; Bhutani, Neha; Clayards, Meghan; Baum, Shari (Frontiers in Language Sciences, 2024)
Learning to understand and speak a new language can be challenging and discouraging for adults. One potential tool for improving learning is transcutaneous auricular vagus nerve stimulation (taVNS), which modulates perception, memory, and attention systems. It has recently been reported that taVNS can improve English speakers' ability to perceive unfamiliar Mandarin tones. The current project explored the potential benefits of taVNS for language learning beyond tone perception. We studied adults' ability to perceive and produce unfamiliar speech sounds as well as any potential change in language learning motivation from pre-to post-training. Forty-five native English speakers were divided into three groups and were trained to perceive German sounds: one group received stimulation during easier-to-learn sounds (vowels), one group received stimulation during harder-to-learn sounds (fricatives), and a control group received no stimulation. We did not find evidence that taVNS improved perception or production of the German sounds, but there was evidence that it did improve some aspects of motivation. Specifically, the group that received taVNS during easier sounds showed a decrease in feelings of tension/pressure about language learning, while the other groups did not. Overall, the present study does not find that taVNS holds benefits for the acquisition of new speech sounds; however, the field is nascent, and so the potential applications of taVNS for language learning remain to be clarified.